PENDAMPINGAN LITERASI KEUANGAN BAGI UMKM DI RUKUN WARGA (RW) 003 KELURAHAN KALISARI - Sukaesih, Uuh; Miswan, Miswan (Jurnal Pengabdian Masyarakat Sabangka, 2023)
More than 90 percent of business activities in Kalisari Village can be categorized as Micro, Small and Medium Enterprises (MSMEs). MSME actors in the Kalisari Village generally experience problems in terms of financial management (financial literacy), even though MSME actors must be able to manage their finances well so that their business activities are successful. efforts regarding financial literacy with the aim of increasing knowledge and being able to overcome financial problems faced. Partners in the activity are 3 business actors in the Rukun Warga area (RW 003 Kelurahan Kalisari, Pasar Rebo District, East Jakarta. Partners are very enthusiastic in participating in business assistance and consulting which is marked by frequent regular consultations. The result of community service activities is partner knowledge regarding literacy financial literacy has increased by 33.81 percent, and problems faced by partners regarding literacy or financial management can be overcome. Assistance activities for partners still need to be continued with material adapted to the problems faced by partners.